A novel bicistronic DNA vaccine with enhanced protective immune response against Bacillus anthracis through DNA prime-protein boost vaccination approach. (September 2021) - Sumithra, T.G.; Chaturvedi, V.K.; Gupta, P.K.; Bincy, J.; Siju, S.J.; Sunita, S.C.; Reshma, K.J.; Patel, C.L.; Rai, A.K.
Abstract: Anthrax, by Bacillus anthracis, remains a dreadful fatal hazard worldwide. The currently used anthrax vaccines are plagued by numerous issues that limit their widespread use. As an immunization approach targeting both extracellular antigens and toxins of B. anthracis may achieve better sterile immunity, the present investigation designed a bicistronic secretory anti-anthrax DNA vaccine targeting immune response against toxin and cells . The efficacy of the vaccine was compared with monocistronic DNA vaccines and the currently used anthrax vaccine. For this, mice were immunized with the developed vaccine containing pag (encoding protective antigen to block toxin) and eag genes (encoding EA1 to target cells) of B. anthracis through DNA-prime/Protein-boost (D/P) and DNA prime/DNA-boost (D/D) approaches. There was a >2 and > 5 fold increase in specific antibody level by D/D and D/P approaches respectively, on 42nd days post-immunization (dpi). Serum cytokine profiling showed that both Th1 and Th2 immune responses were elicited, with more Th2 responses in D/P strategy. More importantly, challenge with 100 times LD50 of B. anthracis at 42nd dpi exhibited maximum cumulative survival (83.33 %) by bicistronic D/P approach. Remarkably, immunization with EA1 delayed mortality onset in infection. The study forms the first report on complement-dependent bactericidal activity of antiEA1 antibodies. In short, co-immunization of PA and EA1 through the developed bicistronic DNA vaccine would be an effective immunization approach in anthrax vaccination. Further, D/P strategy could enhance vaccine-induced immunity against B. anthracis . Altogether, the study generates certain critical insights having direct applications in next-generation vaccine development against anthrax. Highlights: First bicistronic secretory DNA construct targeting toxin and cells of B. anthracis . Points out two effective antigens to be targeted in anthrax vaccination. Sketches an improved immunization strategy against B. anthracis . The immunization elicited both Th1 and Th2 immune response. Immunization with EA1 based vaccines delayed mortality onset in anthrax.